DETERMINASI PROFITABILITAS SEKTOR PERBANKAN DI BURSA EFEK INDONESIA - I Ketut Sudarmanta (Jurnal Ekonomi & Bisnis JAGADITHA, 2016)
Profitability is bank’s ability to get profit during certain period. In order to reach maximal profitability the bank should take attention and to manage the risk which able to have effect on profitability decrease.This study aims to examine the effect ofNet Interest Margin (NIM), BOPO (Operational cost), Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), andNon Performing Loan (NPL) towardReturn On Asset (ROA). Sampling issaturatedthen obtain 30 Bank listed in the Indonesia stock exchange. Data analysis technique applied with multiple regression analysis and hypotesis test by using t-testto examine coefficientregression partiallyand F-testto examine the effect simultaneouslyby significancy level of 5%. Beside that has been conducted assumption classic test covering normality test. During observation period shows that research data is normal distribution. Based on the normality test, multicolinearity test, heteroskedascity test, and autocorrelation test did not find deviate variable from assumption classic. Its shows that data has comply the conditions by using multiple regression analysis. The result shows that variable of NIM, CAR, have positive significant effect toward ROA, while variable of NPL and BOPO have negative effect toward ROA, and LDR don’t have effect toward ROA. Prediction contribution of the seventh varibles toward ROA is 91%, and the rest is 9% effected by other factor that not include in this model of research.